The role of membrane curvature in nanoscale topography-induced intracellular signaling - Lou, Hsin-Ya (2019)
Over the past decade, there has been growing interest in developing biosensors and devices with nanoscale and vertical topography. Vertical nanostructures induce spontaneous cell engulfment, which enhances the cell–probe coupling efficiency and the sensitivity of biosensors. Although local membranes in contact with the nanostructures are found to be fully fluidic for lipid and membrane protein diffusions, cells appear to actively sense and respond to the surface topography presented by vertical nanostructures. For future development of biodevices, it is important to understand how cells interact with these nanostructures and how their presence modulates cellular function and activities. How cells recognize nanoscale surface topography has been an area of active research for two decades before the recent biosensor works. Extensive studies show that surface topographies in the range of tens to hundreds of nanometers can significantly affect cell functions, behaviors, and ultimately the cell fate. For example, titanium implants having rough surfaces are better for osteoblast attachment and host–implant integration than those with smooth surfaces. At the cellular level, nanoscale surface topography has been shown by a large number of studies to modulate cell attachment, activity, and differentiation. However, a mechanistic understanding of how cells interact and respond to nanoscale topographic features is still lacking. In this Account, we focus on some recent studies that support a new mechanism that local membrane curvature induced by nanoscale topography directly acts as a biochemical signal to induce intracellular signaling, which we refer to as the curvature hypothesis. The curvature hypothesis proposes that some intracellular proteins can recognize membrane curvatures of a certain range at the cell-to-material interface. These proteins then recruit and activate downstream components to modulate cell signaling and behavior. We discuss current technologies allowing the visualization of membrane deformation at the cell membrane-to-substrate interface with nanometer precision and demonstrate that vertical nanostructures induce local curvatures on the plasma membrane. These local curvatures enhance the process of clathrin-mediated endocytosis and affect actin dynamics. We also present evidence that vertical nanostructures can induce significant deformation of the nuclear membrane, which can affect chromatin distribution and gene expression. Finally, we provide a brief perspective on the curvature hypothesis and the challenges and opportunities for the design of nanotopography for manipulating cell behavior.